A high-reproducibility organic photovoltaic device based on solid-state relaxation and a preparation method thereof

CN122995502APending Publication Date: 2026-10-27NORTHWESTERN POLYTECHNICAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611048828.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-15
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0007]本发明的目的在于提供一种基于固态弛豫主导形貌演化提高有机光伏器件重现性与加工鲁棒性的方法,以解决现有有机光伏器件中受体材料在成膜阶段快速结晶、活性层形貌对工艺扰动敏感、器件批次间效率波动大和加工鲁棒性不足的问题:

Benefits of technology

[0044]当RSR提高、MAD提高、CV降低且P-FOM提高时,说明该材料体系和工艺条件能够有效提高活性层形貌一致性、器件重现性和加工鲁棒性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122995502A_ABST
    Figure CN122995502A_ABST
Patent Text Reader

Abstract

The application discloses a high-reproducibility organic photovoltaic device based on solid-state relaxation dominated morphology evolution and a preparation method thereof. The method comprises the following steps: monitoring the change of acceptor characteristic absorption peak of an active layer in a film forming stage and a thermal annealing stage by using in-situ ultraviolet-visible absorption spectrum, and calculating the solid-state relaxation contribution proportion according to the peak position displacement amount in the film forming stage and the peak position displacement amount in the thermal annealing stage, so as to determine whether the morphology evolution of the active layer is dominated by the solid-state relaxation stage; when the system has a film forming quenching dominated feature, the diffusion and crystallization ability of the acceptor material in the rapid film forming stage is reduced by increasing the size, steric hindrance or rigidity of the acceptor molecule, and / or adding a morphology dynamics regulating additive, so that the acceptor material is subjected to molecular rearrangement, ordered accumulation, crystallization perfection and phase separation structure optimization in the thermal annealing stage. Preferably, the active layer morphology is changed from being dominated by film forming quenching to being dominated by solid-state relaxation by converting a monomer type acceptor Y6 into a dimer type acceptor DY2 or adding 1,3,5-triiodobenzene in a PM6:L8-BO system. The application also evaluates the active layer morphology consistency, device reproducibility and processing robustness by using the median absolute deviation of the morphology parameters, the coefficient of variation of the device efficiency and the performance quality factor. The organic photovoltaic device prepared by the method has low batch-to-batch efficiency fluctuation and high processing robustness, and is suitable for high-consistency organic photovoltaic devices and large-scale preparation thereof.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of organic photovoltaic materials and device fabrication technology, specifically relating to a highly reproducible organic photovoltaic device and its fabrication method. Background Technology

[0002] Organic photovoltaic (OPV) cells, with their unique advantages such as flexibility, lightweight, semi-transparency, and solution-processability, are considered one of the core directions of next-generation photovoltaic technologies. With the rapid iteration of non-fullerene acceptor materials, the laboratory photoelectric conversion efficiency of single-junction OPV cells has exceeded 21%, initially meeting the performance threshold for industrial applications.

[0003] However, poor performance consistency has become a core bottleneck restricting the transition of organic photovoltaics from the laboratory to industrial production. On the one hand, the performance of devices prepared with the same formula in different batches and by different operators fluctuates significantly, with the efficiency variation coefficient of typical systems being particularly high. CV The yield can reach over 5%, far exceeding the level of less than 0.5% for silicon-based photovoltaics. On the other hand, fluctuations in process parameters such as substrate temperature, solvent evaporation rate, and film thickness are unavoidable in industrial production. The morphology of the active layer of organic photovoltaics is highly sensitive to processing conditions. Even small fluctuations can cause significant differences in phase separation structure and crystallinity, leading to a sharp drop in production yield, i.e., insufficient processing robustness.

[0004] The microstructure of the active layer (crystallinity, phase region size, phase purity, etc.) directly determines exciton dissociation, charge transport, and recombination processes, and is a core factor affecting the consistency of device performance. Existing technologies for improving morphology reproducibility mainly fall into two categories: one is molecular structure optimization, such as reducing polymer defects and controlling molecular weight distribution, which reduces morphology fluctuations by improving intrinsic molecular uniformity; the other is process optimization, such as improving coating methods and precisely controlling solvent evaporation rates, which reduces morphology deviations by improving process controllability. However, the above strategies are all "static optimizations," which can only reduce the impact of disturbances in a single dimension and fail to solve the problem from the dynamic essence of morphology evolution.

[0005] The formation of the active layer morphology involves two fundamentally different stages: the quenching stage during film formation, characterized by rapid solvent evaporation, and the solid-state relaxation stage during post-annealing, characterized by slow molecular rearrangement. The morphology evolution of traditional organic photovoltaic systems is primarily dominated by the quenching stage. Acceptor molecules rapidly crystallize and separate within milliseconds of solvent evaporation, making the morphology highly sensitive to processing conditions and easily frozen in various metastable states with broad energy distributions. This ultimately leads to significant batch-to-batch morphological variations and poor device reproducibility. Furthermore, the crystalline network already formed after film formation raises the phase transition barrier, making it difficult to further optimize and converge the morphology during the annealing stage.

[0006] Based on the above situation, there is currently no effective technical path in this field that can systematically improve the performance reproducibility and processing robustness of organic photovoltaic devices. At the same time, there is also a lack of quantitative evaluation index system for reproducibility and processing robustness. This problem has become the core bottleneck restricting organic photovoltaic technology from the laboratory to large-scale production. Summary of the Invention

[0007] The purpose of this invention is to provide a method for improving the reproducibility and processing robustness of organic photovoltaic devices based on solid-state relaxation-dominated morphology evolution, in order to solve the problems of rapid crystallization of acceptor materials during the film formation stage, sensitivity of active layer morphology to process disturbances, large batch-to-batch efficiency fluctuations, and insufficient processing robustness in existing organic photovoltaic devices. This invention employs in-situ ultraviolet-visible absorption spectroscopy to monitor changes in the characteristic absorption peaks of the receptor in the active layer during the film-forming and thermal annealing stages. The specific implementation scheme is as follows: S1: Characterize the characteristic peaks of the active layer at different stages by in-situ ultraviolet-visible absorption spectroscopy.

[0008] S2: The shift of the characteristic absorption peak of the receptor during the film-forming stage is denoted as Δ. λ film The shift of the characteristic absorption peak of the acceptor during the thermal annealing stage is denoted as Δ. λ anneal And calculate the solid-state relaxation contribution ratio: in, R SR The higher the value, the more likely the ordered stacking and crystallization of the acceptor material will occur during the thermal annealing stage; R SR The lower the value, the faster the acceptor material crystallizes during the film formation stage, and the more easily the morphology of the active layer is affected by solvent evaporation rate, substrate temperature, and film thickness fluctuations.

[0009] S3: If the absorption peak of the acceptor material rapidly red-shifts during the film-forming stage, while the change is small during the annealing stage, then the system is judged to be a film-forming quenching-dominated morphological evolution system, which requires structural or process control.

[0010] S4: If the absorption peak of the acceptor material shows a small red shift during the film formation stage but a large change during the annealing stage, then the system is considered to be a solid-state relaxation-dominated morphological evolution system, and no structural or process control is required.

[0011] S5: Select at least one of the following regulation schemes based on the crystallization ability, diffusion ability, and processing characteristics of the acceptor material.

[0012] S6: By increasing the molecular size, steric hindrance, conformational restriction, or molecular rigidity of the acceptor material, its diffusion and rapid crystallization capabilities during the film-forming stage are reduced.

[0013] S7: Preferably, the monomeric non-fullerene receptor is converted into a dimeric non-fullerene receptor. For example, Y6 is converted into the Y6 dimer derivative DY2.

[0014] S8: The advantage of this scheme is that the larger molecular size and steric hindrance can reduce the long-range diffusion ability of acceptor molecules during the rapid drying process of wet film, making it difficult for them to quickly form a perfect crystalline network during the film formation stage; subsequently, during the thermal annealing stage, acceptor molecules achieve ordered stacking and morphological convergence through solid relaxation.

[0015] S9: In addition, by adding morphology and kinetic regulation additives to the active layer precursor solution, the rapid crystallization of the acceptor material during the film formation stage is delayed.

[0016] S10: Preferably, for the PM6:L8-BO system, a halogenated aromatic additive is added, more preferably 1,3,5-triiodobenzene (1,3,5-TIB).

[0017] S11: The amount of 1,3,5-triiodobenzene added can be 30–100 wt% of the total mass of the donor and acceptor materials, preferably 50–80 wt%.

[0018] S12: The purpose of this scheme is that 1,3,5-triiodobenzene can regulate the crystallization kinetics of L8-BO, suppress its premature ordered stacking during rapid solvent evaporation, and keep the initial film in a metastable state that can be further rearranged; after thermal annealing, L8-BO undergoes ordered stacking and phase separation structure optimization during the solid relaxation stage.

[0019] The donor material, acceptor material, and selected additives are dissolved in the main solvent to form a homogeneous active layer precursor solution.

[0020] The main solvent includes one or more of chloroform, chlorobenzene, o-dichlorobenzene, o-xylene, toluene, trimethylbenzene, tetrahydrofuran, and their mixtures.

[0021] The mass ratio of the donor material to the acceptor material can be 1:(0.6–2.0), preferably 1:(0.8–1.8), and more preferably 1:(1.0–1.5).

[0022] The total concentration of donor and acceptor materials in the active layer precursor solution can be 5–30 mg / mL, preferably 10–25 mg / mL.

[0023] The active layer precursor solution is deposited on the surface of a substrate, a transparent conductive electrode, or a charge transport layer to form an initial wet film.

[0024] Deposition methods include spin coating, blade coating, bar coating, slot coating, spraying, inkjet printing, or roll-to-roll coating.

[0025] During deposition and solvent evaporation, molecular structure regulation or additive regulation can reduce the crystallinity of the acceptor material during the rapid film formation stage, thus avoiding the formation of a fixed crystalline network that is highly sensitive to process disturbances.

[0026] The initial active layer film is subjected to thermal annealing.

[0027] The heat annealing temperature can be 70–200 °C, preferably 90–140 °C.

[0028] The heat annealing time can be 1–30 min, preferably 8–20 min.

[0029] During annealing, acceptor molecules undergo slow diffusion, conformational adjustment, ordered stacking, and crystallization in the solid film. Since the timescale of the thermal annealing stage is longer than that of the film formation stage, the initial differences caused by film formation fluctuations in different batches of films can be gradually reduced through the solid relaxation process, thereby causing the final active layer morphology to converge to similar low-energy metastable states.

[0030] One or more of the following methods were used to verify the crystallization and ordered stacking stages of the acceptor material: in-situ ultraviolet-visible absorption spectroscopy, in-situ fluorescence spectroscopy, in-situ grazing incidence wide-angle X-ray scattering, or molecular dynamics simulation.

[0031] If the system exhibits the following after regulation: the characteristic absorption peak of the receptor decreases red-shift during the film-forming stage, and the absorption peak continues to red-shift during the annealing stage; or the radial distribution function changes little during the film-forming stage, and the peak position blue-shifts and the peak intensity increases during the annealing stage, it indicates that the orderly stacking of the receptor material is delayed from the film-forming stage to the thermal annealing stage, and the morphological evolution of the active layer changes from being dominated by film-forming quenching to being dominated by solid-state relaxation.

[0032] Prepare multiple independent batches of active layer films, with no less than 3 batches for each system, preferably no less than 5 batches; each batch contains no less than 30 devices, preferably no less than 50 devices.

[0033] Morphological characterization was performed on each batch of thin films to obtain at least one or more morphological parameters, including: molecular order; crystal coherence length; phase separation scale; mixed phase ratio; surface roughness; and Urbach energy.

[0034] The testing methods that can be used include grazing incidence wide-angle X-ray scattering (GIWAXS), atomic force microscopy (AFM), transmission electron microscopy (TEM), Raman imaging, and ultraviolet-visible (UV-vis) absorption spectroscopy.

[0035] For the morphological parameters, calculate the absolute deviation of the median: in, x k,i Indicates the first i The first batch k The values ​​of each morphological parameter.

[0036] An organic photovoltaic device is formed by fabricating a charge transport layer and electrodes on the regulated active layer. The device can be an upright or inverted structure. The device structure includes: a transparent conductive electrode / a first charge transport layer / an organic photovoltaic active layer / a second charge transport layer / a metal electrode.

[0037] Multiple independent batches of devices are prepared under the same process conditions, with no less than 3 batches for each system, preferably no less than 5 batches; the number of devices in each batch is no less than 10, preferably no less than 30.

[0038] Testing each device V OC , J SC FF and PCE, and using the PCE coefficient of variation ( CV Evaluate device reproducibility: in, σ The standard deviation of PCE for multiple devices, μ This represents the average PCE of multiple devices. CV The lower the value, the more concentrated the device efficiency distribution and the higher the device reproducibility.

[0039] Devices are fabricated under different processing disturbance conditions, including: substrate temperature variation; active layer thickness variation; annealing temperature variation; solvent system variation; coating speed variation; and ambient temperature and humidity variation.

[0040] Test the open-circuit voltage of the device under different disturbance conditions. V OC ), short-circuit current density ( J SC ), fill factor (FF) and power conversion efficiency (PCE), and calculate the performance quality factor (). P-FOM ): in, j Indicates device performance parameters, including V OC , J SC FF and PCE; ω j The weights of each performance parameter; μ jThis represents the average value of the corresponding performance parameter; X j,max This represents the maximum value of this performance parameter under different process conditions; CV j This is the coefficient of variation for this performance parameter.

[0041] P-FOM The closer the value is to 1, the higher the performance and the lower the fluctuation of the device under different process disturbances, and the higher the processing robustness.

[0042] according to R SR , MAD , CV and P-FOM The results provide feedback to optimize molecular structure, additive types, additive ratios, annealing temperature, annealing time, solvent system, and coating method.

[0043] when R SR Lower MAD Lower CV higher or P-FOM At lower values, it indicates that the morphology of the active layer is still significantly affected by the film-forming quenching process, and further enhancement of the solid-state relaxation contribution is needed. The following optimization methods can be adopted: increasing the acceptor molecular size or steric hindrance; selecting dimer-type or low-diffusion-type acceptor materials; increasing the proportion of morphology kinetic control additives; adjusting the annealing temperature and annealing time; changing the solvent system to adjust the film formation rate; and optimizing the film thickness and coating speed.

[0044] when R SR improve, MAD improve, CV Lower and P-FOM The improvement indicates that the material system and process conditions can effectively improve the consistency of the active layer morphology, device reproducibility, and processing robustness. Attached Figure Description

[0045] Figure 1 These are in-situ UV-vis contour plots and peak-time variation diagrams of the PM6:Y6 system during film formation and post-annealing. Figure 2 These are in-situ UV-vis contour plots and peak-time variation diagrams of the PM6:DY2 system during film formation and post-annealing. Figure 3 It refers to the Urbach energy of PM6:Y6 in different batches; Figure 4 It is the Urbach energy of PM6:DY2 in different batches; Figure 5 These are the peak values ​​of the UV-Vis absorption spectra of PM6:Y6 in different batches; Figure 6 These are the peak values ​​of the UV-Vis absorption spectra of PM6:DY2 from different batches; Figure 7 These are Raman images of PM6:Y6 from different batches; Figure 8 These are Raman images of PM6:DY2 from different batches; Figure 9 These are atomic force microscope height diagrams of PM6:Y6 from different batches; Figure 10 These are atomic force microscopy height diagrams of PM6:DY2 from different batches; Figure 11 The statistical distribution of PCE and corresponding values ​​for PM6:Y6 devices in five independent fabrication batches are shown. CV contrast; Figure 12 The statistical distribution of PCE and corresponding values ​​for PM6:DY2 devices in five independent fabrication batches are shown. CV contrast; Figure 13 This is a two-dimensional correlation distribution of photovoltaic parameters for PM6:Y6 and PM6:DY2 devices under varying substrate temperature. Figure 14 This is a two-dimensional correlation distribution of photovoltaic parameters for PM6:Y6 and PM6:DY2 devices under varying active layer thickness. Figure 15 This is a two-dimensional correlation distribution of photovoltaic parameters for PM6:Y6 and PM6:DY2 devices under varying annealing temperatures; Figure 16 The PM6:Y6 and PM6:DY2 devices are in o -Two-dimensional correlation distribution of photovoltaic parameters under XY processing temperature variations; Figure 17 These are in-situ UV-vis contour plots and peak position-time variation diagrams of the PM6:L8-BO system during film formation and post-annealing under 1,2,4-TCB conditions. Figure 18 These are in-situ UV-vis contour plots and peak position-time variation plots of the PM6:L8-BO system during film formation and post-annealing under 1, 3, 5-TIB conditions. Figure 19 The statistical distribution of PCE in the PM6:L8-BO system under 1, 2, 4-TCB conditions in five independent preparation batches and the corresponding values. CV contrast; Figure 20 The statistical distribution of PCE and corresponding values ​​in five independent batches of the PM6:L8-BO system prepared under 1, 3, and 5-TIB conditions are shown. CVcontrast; Figure 21 The two-dimensional correlation distribution of photovoltaic parameters of the PM6:L8-BO system under substrate temperature variations under 1,2,4-TCB and 1,3,5-TIB conditions is shown. Figure 22 The two-dimensional correlation distribution of photovoltaic parameters of the PM6:L8-BO system under the conditions of 1,2,4-TCB and 1,3,5-TIB with varying active layer thickness is shown. Figure 23 The two-dimensional correlation distribution of photovoltaic parameters of the PM6:L8-BO system under annealing temperature variations of 1,2,4-TCB and 1,3,5-TIB conditions is shown. Figure 24 The PM6:L8-BO system under 1,2,4-TCB and 1,3,5-TIB conditions o -Two-dimensional correlation distribution of photovoltaic parameters under XY processing temperature variations.

[0046] Figure 25 This is a summary drawing of the specification of this invention. Detailed Implementation

[0047] The present invention will be further described in detail below with reference to specific embodiments, but the implementation of the present invention is not limited thereto.

[0048] Unless otherwise specified, the device fabrication in the following examples and comparative examples can be carried out according to the following methods.

[0049] The ITO glass substrate was ultrasonically cleaned sequentially with glass cleaner, deionized water, acetone, and isopropanol, each step lasting 15 minutes. After cleaning, the ITO substrate was dried in a 100 °C oven for 20 minutes, followed by treatment in a UV ozone cleaner for 15 minutes to remove organic contaminants from the ITO surface and improve its surface wettability. The hole transport layer employs a double-layer structure. First, 0.3 mg / mL... 1 A 40 μL solution of 2PACz methanol was dropwise onto the ITO surface and spin-coated at 3000 rpm for 30 s, followed by annealing at 80 °C for 8 min; then, a second UV ozone treatment was performed for 15 min. After the hole transport layer was prepared, the substrate was transferred to a glove box for active layer preparation. The substrate cleaning, hole transport layer preparation, and subsequent device structure conditions described above are all derived from the device fabrication section of this document.

[0050] After the active layer was prepared, PNDIT-F3N was spin-coated onto the surface of the active layer as an electron transport layer. Specifically, 0.5 mg / mL of PNDIT-F3N was prepared. 4The PNDIT-F3N methanol solution was spin-coated at 2200 rpm for 30 s. Subsequently, the sample was transferred through a mask into a thermal evaporation chamber, where the chamber vacuum level was below 2 × 10⁻⁶. 4 After mbar deposition, an Al electrode with a thickness of 100 nm was deposited at a deposition rate of 0.8 Å / s. 1 The effective area of ​​the device is 0.05 cm². 2 The device's current density - voltage ( JV Tested at AM 1.5G, 100 mW cm 2 The voltage scan was performed under illumination, with a range of [missing information]. The scanning step size is 0.2 to 1.0 V, with a step size of 0.02 V; the EQE test wavelength range is 300–1100 nm, with an interval of 10 nm.

[0051] Comparative Example 1 This comparative example illustrates that the traditional monomeric receptor Y6 tends to form a film-forming quenching-dominated morphology in the PM6:Y6 active layer, which leads to further limitation of morphological evolution in the post-annealing stage.

[0052] The donor material used in this comparative example is PM6, and its molecular structure is as follows: The donor material used in this comparative example is Y6, and its molecular structure is as follows: PM6 and Y6 were dissolved in an organic solvent at a predetermined mass ratio to prepare a PM6:Y6 active layer precursor solution. This solution was deposited on the surface of the hole transport layer to form an initial wet film. After solvent evaporation, an initial PM6:Y6 active layer film was obtained. Subsequently, the film was subjected to thermal annealing to prepare the PM6:Y6 active layer and the corresponding organic photovoltaic device.

[0053] In-situ UV-Vis absorption spectroscopy was used to monitor the absorption peak evolution of the PM6:Y6 active layer during the film formation and annealing stages in real time. The results showed that in the PM6:Y6 system, the characteristic absorption peak of Y6 rapidly red-shifted from approximately 730 nm to approximately 780 nm during film formation, while only a slight shift occurred during the post-annealing stage. This result indicates that the ordered molecular stacking and crystallization of Y6 mainly occurred during the rapid film formation stage, with the post-annealing stage contributing little further to the crystallization process.

[0054] Based on the above data, the shift of the characteristic absorption peak of Y6 during the film formation stage is denoted as Δλ. film The shift of the characteristic absorption peak of Y6 during the annealing stage is denoted as Δλ. annealAnd calculate the solid-state relaxation contribution ratio R. SR The value is 0.09. For the PM6:Y6 system, due to Δλ film Much greater than Δλ anneal Therefore R SR The high value indicates that the system belongs to the film-forming quenching-dominated morphology evolution system.

[0055] To further evaluate the morphological reproducibility of the PM6:Y6 active layer, multiple independent batches of PM6:Y6 active layer films were prepared. For each system, at least three independent batches were prepared, preferably at least five independent batches, and more preferably at least ten independent batches.

[0056] Systematic morphological characterization was performed on PM6:Y6 films from different batches. First, the ratio of ordered and disordered phases in different batches of films was analyzed using UV-Vis absorption spectroscopy peak segmentation. Second, Urbach energy was obtained using FTPS-EQE or absorption edge fitting methods to characterize the energy disorder of the active layer. Third, the proportions of donor, acceptor, and blended phases were statistically analyzed using Raman imaging combined with image segmentation. Finally, AFM was used to obtain the surface roughness and phase region morphology of films from different batches.

[0057] The results show that although the PM6:Y6 system can form a relatively stable fine phase region structure after film formation, its main morphology is fixed during the rapid film formation stage, and different batches of films are easily frozen in different metastable structures. Therefore, this system exhibits large batch-to-batch fluctuations in key morphological parameters such as Urbach energy, crystallinity, surface roughness, and blending phase ratio. The results show that the Urbach energy of the PM6:Y6 system has a wide fluctuation range, with a MAD of 0.72 meV; the crystallinity fluctuation range exceeds 8.5%, with a MAD of 2.67%.

[0058] To evaluate the impact of film-forming quenching-dominant morphology on device reproducibility, five independent batches of PM6:Y6 organic photovoltaic devices were continuously fabricated under identical process conditions, with 30 devices per batch, totaling 150 independent devices. The identical process conditions included the same donor-acceptor ratio, the same solvent system, the same active layer thickness, the same annealing conditions, and the same device structure.

[0059] The PCE of PM6:Y6 devices ranges from 15.08% to 17.12%, with variations across different batches. CV The PCE ranges from 2.14% to 2.95%; statistically, for all 150 devices, the average PCE for PM6:Y6 is 16.14%, with batch-to-batch differences. CV It is 3.06%.

[0060] To further evaluate the sensitivity of PM6:Y6 devices to process disturbances, multiple sets of PM6:Y6 devices were fabricated by varying the substrate temperature, active layer thickness, annealing temperature, and green solvent processing temperature. Specifically, the substrate temperature was set to 30, 45, and 60 °C; the active layer thickness was set to approximately 100, 200, and 300 nm; the annealing temperature was set to 80, 100, and 120 °C; o-xylene was used as the green solvent system, and the processing temperature was set to 100, 110, and 120 °C.

[0061] The results show that, under four types of disturbances—substrate temperature, active layer thickness, annealing temperature, and green solvent processing temperature—PM6:Y6... P-FOM The values ​​are 0.925, 0.914, 0.928 and 0.912, respectively.

[0062] Example 1 This embodiment illustrates a technical solution for improving the reproducibility and fabrication robustness of organic photovoltaic devices through molecular structure regulation.

[0063] The donor material used in this Example 1 is the same as that in Comparative Example 1.

[0064] The donor material used in this embodiment is DY2, and its molecular structure is as follows: PM6 and DY2 were dissolved in an organic solvent at a predetermined mass ratio to prepare a PM6:DY2 active layer precursor solution. DY2 is a dimer derivative of Y6. Compared to Y6, DY2 has a larger molecular size and steric hindrance, which reduces its diffusion ability and rapid crystallization ability during film formation. This solution was deposited on the surface of the hole transport layer to form an initial wet film. After solvent evaporation, an initial PM6:DY2 thin film was formed. Subsequently, thermal annealing was performed to allow DY2 to undergo molecular diffusion, ordered stacking, perfect crystallization, and phase separation structure optimization in the solid film, resulting in the PM6:DY2 active layer and the corresponding device.

[0065] In-situ UV-Vis absorption spectroscopy was used to monitor the evolution of absorption peaks during the film formation and annealing processes of the PM6:DY2 active layer. The results showed that the absorption peak of DY2 only slowly red-shifted from approximately 735 nm to approximately 750 nm during film formation, while it continued to red-shift to approximately 790 nm during the annealing stage. Compared to the PM6:Y6 system, acceptor crystallization and ordered stacking of PM6:DY2 did not primarily occur during the rapid film formation stage, but were significantly delayed until the post-annealing stage.

[0066] Calculate R based on the above data. SR The value is 0.73. For the PM6:DY2 system, R... SRThe significant improvement indicates that the morphological evolution of this system is mainly dominated by the post-annealing solid-state relaxation stage.

[0067] To evaluate the morphological reproducibility of the PM6:DY2 active layer, multiple independent batches of PM6:DY2 active layer films were prepared under the same preparation conditions as the PM6:Y6 comparative example. Each system had at least three independent batches, preferably at least five, and more preferably at least ten.

[0068] Multiple independent batches of PM6:DY2 active layer films were prepared under the same preparation conditions as the comparative example. The morphological parameters of the films from each batch were then obtained using UV-vis peak fractionation, Raman imaging, AFM, and GIWAXS, and the MAD (Magnitude of Deposition) was calculated.

[0069] Test results show that the PM6:DY2 system exhibits smaller fluctuations in morphological parameters across different batches. The document shows that the Urbach energy of PM6:DY2 is mainly distributed in the range of 21.79–22.75 meV, with the MAD decreasing to 0.19 meV; the crystallinity fluctuation spans 4.77%, and the MAD decreases to 1.85%, both significantly lower than those of the PM6:Y6 system.

[0070] To evaluate the batch-to-batch reproducibility of PM6:DY2 devices, five independent batches of PM6:DY2 organic photovoltaic devices were continuously fabricated under the same process conditions as the PM6:Y6 comparative example, with 30 devices per batch, for a total of 150 independent devices. The identical process conditions included the same donor-acceptor ratio, the same solvent system, the same active layer thickness, the same annealing conditions, and the same device structure.

[0071] Five independent batches of devices were prepared under the same process conditions as Comparative Example 1, with 30 devices in each batch, for a total of 150 independent devices. All devices were then subjected to… JV Test, obtain V OC , J SC FF and PCE, and using the PCE coefficient of variation. CV Evaluate the reproducibility of the device.

[0072] The PCE of PM6:DY2 devices is concentrated in the range of 17.25%–18.30%, within each batch. CV The PCE ranges from 1.19% to 1.39%; statistically, for all 150 devices, the average PCE for PM6:DY2 is 17.74%, with batch-to-batch differences. CV It was only 1.43%.

[0073] To evaluate the tolerance of PM6:DY2 devices to processing disturbances, this embodiment uses the PM6:DY2 system. Following the same method as Comparative Example 1, multiple groups of PM6:DY2 devices were fabricated by varying the substrate temperature, active layer thickness, annealing temperature, and green solvent processing temperature. The performance of each group of devices was then tested. V OC , J SC FF and PCE, and calculate P-FOM .

[0074] Test results show that, under four types of disturbances—substrate temperature, active layer thickness, annealing temperature, and green solvent processing temperature—PM6:DY2... P-FOM The values ​​were 0.944, 0.929, 0.950, and 0.931, respectively, all higher than the corresponding values ​​for PM6:Y6; the average values ​​under the four conditions... P-FOM The value was 0.939, which was significantly higher than the 0.920 of PM6:Y6. This indicates that PM6:DY2 has good reproducibility and processing robustness.

[0075] Comparative Example 2 This comparative example illustrates that the PM6:L8-BO system still exhibits strong morphological evolution characteristics during the film-forming stage under traditional 1,2,4-TCB additive conditions.

[0076] The donor material used in Comparative Example 2 is the same as that in Comparative Example 1.

[0077] The donor material used in Comparative Example 2 is L8-BO, and its molecular structure is as follows: The additive used in this embodiment is 1,2,4-TCB, whose molecular structural formula is: PM6 and L8-BO were dissolved in chloroform at a predetermined mass ratio, and 1,2,4-trichlorobenzene was added as an additive. The mixture was stirred to obtain a homogeneous active layer precursor solution. This solution was deposited on the surface of the hole transport layer to form an initial wet film. After solvent evaporation, an initial PM6:L8-BO / 1,2,4-TCB thin film was formed, and then subjected to thermal annealing to prepare the corresponding organic photovoltaic device.

[0078] In-situ UV-Vis absorption spectroscopy was used to monitor the changes in the characteristic absorption peaks of L8-BO during film formation and post-annealing. In the 1,2,4-TCB system, the characteristic absorption peaks of L8-BO underwent a significant red shift during the film formation stage, while the peak position changes were weaker during the annealing stage, indicating that its ordered stacking and crystallization mainly occurred during the film formation stage. Molecular dynamics simulations also showed that under 1,2,4-TCB conditions, L8-BO rapidly aggregated and formed a relatively stable structure during film formation.

[0079] This comparative example is used to illustrate that PM6:L8-BO devices under the 1,2,4-TCB additive system still exhibit significant batch-to-batch efficiency fluctuations.

[0080] This comparative example uses the PM6:L8-BO / 1,2,4-TCB system. Five independent batches of devices were fabricated under the same standard process conditions, with 30 devices per batch, for a total of 150 devices. Each device was then subjected to... JV Test and calculate the PCE coefficient of variation. CV .

[0081] Test results show that the PCE of PM6:L8-BO / 1,2,4-TCB devices ranges from 18.06% to 19.25%, with variations across different batches. CV The PCE ranges from 1.55% to 1.96%; a comprehensive statistical analysis of all 150 devices shows an average PCE of 18.71%, with batch-to-batch variations. CV It is 1.85%.

[0082] This comparative example is used to illustrate the tolerance of the conventional 1,2,4-TCB additive system to process disturbances.

[0083] This comparative example uses the PM6:L8-BO / 1,2,4-TCB system. Multiple devices were fabricated and tested by varying the substrate temperature, active layer thickness, annealing temperature, and green solvent processing temperature. V OC , J SC , FF and PCE.

[0084] Under varying substrate temperature conditions, when the temperature increased from 30 ℃ to 60 ℃, the PCE of the 1,2,4-TCB system decreased from 19.27% ​​to 18.09%; under varying active layer thickness conditions, when the thickness increased from 100 nm to 300 nm, the PCE decreased from 19.36% to 18.15%; under processing conditions with the green solvent o-xylene, the PCE remained within the range of 16.94%–17.41%, with significant fluctuations.

[0085] Further calculations P-FOMThe 1,2,4-TCB system under four conditions: substrate temperature, active layer thickness, annealing temperature, and green solvent processing temperature. P-FOM The values ​​are 0.935, 0.931, 0.954 and 0.936, respectively.

[0086] Example 2 This embodiment illustrates a technical solution for improving the reproducibility and processing robustness of organic photovoltaic devices through additive engineering.

[0087] The donor material used in this Example 2 is the same as that in Comparative Example 1.

[0088] The receptor material used in Example 2 is the same as that in Comparative Example 2.

[0089] The additive used in this embodiment is 1,3,5-TIB, whose molecular structural formula is: PM6 and L8-BO were dissolved in chloroform at a mass ratio of 1:(1.0–1.5) to make the total concentration of donor and acceptor materials 10–25 mg / mL. - ¹. Subsequently, 1,3,5-triiodobenzene was added as a morphology and kinetic control additive, wherein the amount of 1,3,5-triiodobenzene added was 0.5–20 wt% of the total mass of PM6 and L8-BO, preferably 1–10 wt%, more preferably 2–6 wt%. The resulting solution was stirred at room temperature or 30–60 °C for 2–12 h to obtain a homogeneous active layer precursor solution.

[0090] The solution was deposited on the surface of the hole transport layer to form an initial wet film. After solvent evaporation, an initial PM6:L8-BO / 1,3,5-TIB thin film was formed. The film was then thermally annealed at 70–140 °C for 1–30 min, preferably at 90–120 °C for 5–20 min, to allow L8-BO to undergo ordered stacking, improved crystallization, and optimized phase separation structure during the solid-state relaxation stage. After annealing, the electron transport layer and Al electrode were fabricated according to general device fabrication methods.

[0091] In-situ UV-Vis absorption spectroscopy was used to characterize the film formation and annealing processes of L8-BO. ​​The results showed that in the 1,3,5-TIB system, the absorption peak of L8-BO exhibited a small red shift during the film formation stage, while a sustained red shift occurred during the annealing stage. This indicates that 1,3,5-TIB can inhibit the rapid crystallization of L8-BO during the film formation stage and postpone its ordered stacking process to the post-annealing solid-state relaxation stage. Molecular dynamics simulations further revealed that in the 1,3,5-TIB system, the aggregation of L8-BO was weak during the film formation stage, while intermolecular stacking was enhanced during the annealing stage, indicating that 1,3,5-TIB can effectively alter the crystallization kinetics of L8-BO.

[0092] Furthermore, this embodiment uses the PM6:L8-BO / 1,3,5-TIB system. Five independent batches of devices were fabricated under the same standard process conditions as Comparative Example 1, with 30 devices per batch, for a total of 150 devices. Each device was then subjected to… JV Test and calculate PCE. CV .

[0093] Test results show that the PCE distribution of PM6:L8-BO / 1,3,5-TIB devices is concentrated in the range of 18.65%–19.57%, and varies across batches. CV The PCE ranges from 1.02% to 1.28%; a comprehensive statistical analysis of all 150 devices shows an average PCE of 19.11%, with batch-to-batch variations. CV It is only 1.14%.

[0094] Meanwhile, this embodiment uses the PM6:L8-BO / 1,3,5-TIB system. Following the same method as Comparative Example 1, multiple devices were fabricated and tested by varying the substrate temperature, active layer thickness, annealing temperature, and green solvent processing temperature. V OC , J SC , FF and PCE.

[0095] Under varying substrate temperature conditions, when the temperature increased from 30 ℃ to 60 ℃, the PCE of the 1,3,5-TIB system decreased only from 19.43% to 18.95%. Under varying active layer thickness conditions, when the thickness increased from 100 nm to 300 nm, the PCE decreased from 19.46% to 18.77%. Under processing conditions with the green solvent o-xylene, the PCE of the 1,3,5-TIB system ranged from 17.15% to 17.89%, and its overall performance was higher than that of the 1,2,4-TCB system.

[0096] Further calculations P-FOM The 1,3,5-TIB system under four conditions: substrate temperature, active layer thickness, annealing temperature, and green solvent processing temperature. P-FOM The values ​​were 0.955, 0.945, 0.968 and 0.943, respectively, all higher than the 1,2,4-TCB system, indicating good processing robustness.

[0097] The above description, in conjunction with specific preferred embodiments, provides a further detailed explanation of the present invention. It should not be construed that the specific implementation of the present invention is limited to these descriptions. For those skilled in the art, various simple deductions or substitutions can be made without departing from the concept of the present invention, and all such modifications and substitutions should be considered within the scope of protection of the present invention.

Claims

1. A method for fabricating a highly reproducible organic photovoltaic device based on solid-state relaxation-dominated morphology evolution, characterized in that, Includes the following steps: S1, Select donor materials and non-fullerene acceptor materials to prepare organic photovoltaic active layer precursor solutions; S2, In-situ ultraviolet-visible absorption spectroscopy was used to monitor the changes in the characteristic absorption peaks of the acceptor in the organic photovoltaic active layer during the film formation and thermal annealing stages; S3, the shift of the characteristic absorption peak of the receptor during the film-forming stage is denoted as Δ. λ film The shift of the characteristic absorption peak of the acceptor during the thermal annealing stage is denoted as Δ. λ anneal And according to Δ λ film and Δ λ anneal Calculate the solid-state relaxation contribution ratio R SR ; S4. Determine whether the morphological evolution of the organic photovoltaic active layer is dominated by the solid-state relaxation stage based on the solid-state relaxation contribution ratio. S5, when the organic photovoltaic active layer exhibits a film-forming quenching-dominated morphological evolution, the diffusion ability, aggregation ability, or rapid crystallization ability of the non-fullerene acceptor material during the film-forming stage is reduced by molecular structure regulation and / or additive regulation. S6, deposit the regulated active layer precursor solution onto the surface of the substrate, transparent conductive electrode or charge transport layer to form an initial wet film; S7, the solvent in the initial wet film evaporates to form an initial active layer film; S8, the initial active layer film is subjected to thermal annealing treatment, so that the non-fullerene acceptor material undergoes molecular rearrangement, ordered stacking, perfect crystallization and phase separation structure optimization in the solid relaxation stage; S9, a charge transport layer and electrodes are prepared on the organic photovoltaic active layer to obtain an organic photovoltaic device.

2. The preparation method according to claim 1, characterized in that, The contribution ratio of solid-state relaxation R SR ,in, R SR The higher the value, the more likely the ordered stacking and crystallization of the non-fullerene acceptor material is to occur during the thermal annealing stage; R SR The lower the value, the more likely the ordered stacking and crystallization of the non-fullerene acceptor material will occur during the film-forming stage.

3. The preparation method according to claim 1, characterized in that, When the characteristic absorption peak of the non-fullerene acceptor material rapidly red-shifts during the film-forming stage, while the shift of the characteristic absorption peak during the thermal annealing stage is relatively small, the organic photovoltaic active layer is determined to be a film-forming quenching-dominated morphological evolution system.

4. The preparation method according to claim 1, characterized in that, When the red shift of the characteristic absorption peak of the non-fullerene acceptor material is small during the film-forming stage, but continues to red shift during the thermal annealing stage, the organic photovoltaic active layer is determined to be a solid-state relaxation-dominated morphological evolution system.

5. The preparation method according to claim 1, characterized in that, The molecular structure regulation includes increasing the molecular size, steric hindrance, conformational restriction, or molecular rigidity of the non-fullerene acceptor material to reduce its long-range diffusion and rapid crystallization capabilities during the rapid film formation stage.

6. As described in claim 5, characterized in that, The molecular structure regulation includes converting monomeric non-fullerene receptors into dimeric non-fullerene receptors.

7. The preparation method according to claim 1, characterized in that, The additive regulation includes adding morphology and kinetic regulation additives to the active layer precursor solution to delay the rapid crystallization of the non-fullerene acceptor material during the film formation stage.

8. As described in claim 7, characterized in that, The morphology and kinetics regulating additives include halogenated aromatic additives.

9. As described in claim 8, characterized in that, The additive content is 20–100 wt% of the total mass of the non-fullerene acceptor material, preferably 50–80 wt%.

10. The preparation method according to claim 1, characterized in that, The donor material includes one or more of PM6, D18, PBDB-T, PTQ10, PM7 and their derivatives.

11. The preparation method according to claim 1, characterized in that, The non-fullerene acceptor materials include one or more of Y6, DY2, L8-BO and their derivatives.

12. The preparation method according to claim 1, characterized in that, The mass ratio of the donor material to the non-fullerene acceptor material is 1:(0.6–2.0), preferably 1:(0.8–1.5).

13. The preparation method according to claim 1, characterized in that, The total concentration of donor material and non-fullerene acceptor material in the active layer precursor solution is 5–30 mg / mL, preferably 10–25 mg / mL.

14. The preparation method according to claim 1, characterized in that, The main solvent in the active layer precursor solution includes one or more of chloroform, chlorobenzene, o-dichlorobenzene, o-xylene, toluene, trimethylbenzene, tetrahydrofuran, and their mixtures.

15. The preparation method according to claim 1, characterized in that, The active layer precursor solution is deposited by spin coating, doctor blade coating, bar coating, slot coating, spraying, inkjet printing, or roll-to-roll coating.

16. The preparation method according to claim 1, characterized in that, The temperature of the heat annealing treatment is 70–200℃, preferably 90–140℃; the time of the heat annealing treatment is 1–30 min, preferably 8–20 min.

17. The preparation method according to claim 1, characterized in that, The organic photovoltaic device is either upright or inverted.

18. The preparation method according to claim 17, characterized in that, The organic photovoltaic device includes a transparent conductive electrode (ITO, FTO), a first charge transport layer (PEDOT:PSS, 2PACz and its derivatives, ZnO), an organic photovoltaic active layer, a second charge transport layer (PDINN, PFN, PNDIT-F3N, MoO3), and a metal electrode (Ag, Al) arranged sequentially.

19. The preparation method according to claim 1, characterized in that, It also includes evaluating the morphological consistency of multiple independent batches of active layer films. The morphological consistency evaluation includes: preparing no less than 3 independent batches of active layer films; obtaining morphological parameters using one or more of the following testing methods: GIWAXS, AFM, TEM, Raman imaging, UV-Vis absorption spectroscopy, or FTPS-EQE; calculating the median absolute deviation (MAD) based on the morphological parameters; and evaluating the morphological consistency of different batches of active layer films based on the MAD.

20. The preparation method according to claim 19, characterized in that, The morphological parameters include one or more of the following: molecular order, crystal coherence length, phase separation scale, mixed phase ratio, surface roughness, and Urbach energy.

21. The preparation method according to claim 1, characterized in that, It also includes evaluating the reproducibility of organic photovoltaic devices from multiple independent batches. This reproducibility evaluation includes: fabricating no fewer than three independent batches of organic photovoltaic devices under the same process conditions; and testing the open-circuit voltage of each device. V OC ), short-circuit current density ( J SC ), fill factor (FF), and power conversion efficiency (PCE); the coefficient of variation of PCE is calculated based on the standard deviation and mean of PCE. CV );according to CV Evaluate the reproducibility of the organic photovoltaic device.

22. The preparation method according to claim 1, characterized in that, The evaluation also includes a fabrication robustness assessment of the organic photovoltaic device, comprising: fabricating the organic photovoltaic device under different fabrication perturbation conditions; and testing the device under different fabrication perturbation conditions. V OC , J SC FF and PCE; calculate the performance quality factor based on the average, maximum, and coefficient of variation of each performance parameter under different processing disturbance conditions. P-FOM );according to P-FOM The fabrication robustness of the organic photovoltaic device was evaluated.

23. The preparation method according to claim 22, characterized in that, The processing disturbance conditions include one or more of the following: substrate temperature change, active layer thickness change, annealing temperature change, solvent system change, coating speed change, and ambient temperature and humidity change.

24. The preparation method according to claim 23, characterized in that, when R SR Lower, MAD higher CV higher or P-FOM At lower levels, the contribution of solid-state relaxation can be enhanced by increasing the size or steric hindrance of the acceptor molecules, selecting dimer or low-diffusion acceptor materials, adjusting the proportion of additives to regulate morphology and kinetics, adjusting the annealing temperature and annealing time, changing the solvent system, or optimizing the film thickness and coating speed.

25. A highly reproducible organic photovoltaic device, characterized in that, The organic photovoltaic device is prepared by the preparation method according to any one of claims 1 to 24.